2016
DOI: 10.4238/gmr15048852
|View full text |Cite
|
Sign up to set email alerts
|

Genome-wide identification and expression analysis of CIPK genes in diploid cottons

Abstract: Calcineurin B-like protein-interacting protein kinase (CIPK) plays a key regulatory role in the growth, development, and stress resistance of plants by combining with phosphatase B subunit-like protein. In the present study, CIPK genes were identified in the whole genomes of diploid cottons and their sequences were subjected to bioinformatic analyses. The results demonstrated that the CIPK gene family was unevenly distributed in two diploid cotton genomes. Forty-one CIPKs were identified in the D genome, mainl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 27 publications
0
9
0
Order By: Relevance
“…Two genomes of allotetraploid cotton species (G. hirsutum and G. barbadense) underwent a diploidization following the divergence of G. arboreum (A genome) and G. raimondii (D genome). Based on the genome scans of two diploid cotton species, the CIPK gene family was investigated in G. raimondii (41) and G. arboreum (39) [19]. To clarify the divergence during cotton evolution, we analyzed the orthologous CIPK genes between G. raimondii, G. arboreum, and the A and D subgenomes of the two allotetraploid species (G. hirsutum and G. barbadense) (Table S5, Figure S1).…”
Section: Identification Of Cipk Genes In G Hirsutum and G Barbadensementioning
confidence: 99%
See 2 more Smart Citations
“…Two genomes of allotetraploid cotton species (G. hirsutum and G. barbadense) underwent a diploidization following the divergence of G. arboreum (A genome) and G. raimondii (D genome). Based on the genome scans of two diploid cotton species, the CIPK gene family was investigated in G. raimondii (41) and G. arboreum (39) [19]. To clarify the divergence during cotton evolution, we analyzed the orthologous CIPK genes between G. raimondii, G. arboreum, and the A and D subgenomes of the two allotetraploid species (G. hirsutum and G. barbadense) (Table S5, Figure S1).…”
Section: Identification Of Cipk Genes In G Hirsutum and G Barbadensementioning
confidence: 99%
“…It was reported that CIPK genes participate in plant growth and development, and play critical roles in various stresses, including abiotic stresses and hormones [15,18]. The expression levels of CIPK genes in G. raimondii and G. arboreum were induced under abiotic stresses (drought, salt and low temperature) [19]. In Arabidopsis, the expression level of AtCIPK3 was enhanced during the early developmental stages of seedlings, and the Atcipk3 mutant showed high sensitivity under abscisic acid (ABA) stress during seed germination [20], and overexpression of GhCIPK6 increased tolerance to salt, drought, and ABA stresses in transgenic Arabidopsis [21].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…CBLs generally interact with CIPKs to form CBL-CIPK complexes that regulate downstream target proteins. CIPK proteins and CBL-CIPK complexes were involved in various responsive processes in Arabidopsis and other plants, such as rice (Oryza sativa) [26][27][28][29], maize (Zea mays) [30][31][32], Populus euphratica [33,34], canola (Brassica napus) [35,36], eggplant (Solanum melongena) [37], tomato (Solanum lycopersicum) [38], foxtail millet (Setaria italica (L.) P. Beauv) [39], pineapple (Ananas comosus) [40] and cotton [41][42][43][44]. CIPKs and CBL-CIPK complex have been implicated in the plant's response to abiotic stresses, biotic stresses, phytohormones, and nutrient deprivation [45][46][47][48][49][50].…”
Section: Introductionmentioning
confidence: 99%
“…CBLs generally interact with CIPKs to form CBL-CIPK complexes that regulate downstream target proteins. CIPK proteins and CBL-CIPK complexes were involved in various responsive processes in Arabidopsis and other plants, such as rice (O. sativa) [26][27][28][29], maize (Zea mays) [30][31][32], Populus euphratica [33,34], canola (B. napus) [35,36], eggplant (Solanum melongena) [37], tomato (Solanum lycopersicum) [38], foxtail millet (Setaria italica (L.) P. Beauv) [39], pineapple (Ananas comosus) [40] and cotton [41][42][43][44]. CIPKs and CBL-CIPK complex have been implicated in the plant's response to abiotic stresses, biotic stresses, phytohormones, and nutrient deprivation [45][46][47][48][49][50].…”
Section: Introductionmentioning
confidence: 99%